Spurious HbA1c results in patients with diabetes treated with dapsone. (27th September 2019) - Aljenaee, Khaled; Hakami, Osamah; Davenport, Colin; Farrell, Gemma; Tun, Tommy Kyaw; Pazderska, Agnieszka; Phelan, Niamh; Healy, Marie-Louise; Sreenan, Seamus; McDermott, John H
Abstract : Summary: Measurement of glycated haemoglobin (HbA1c) has been utilised in assessing long-term control of blood glucose in patients with diabetes, as well as diagnosing diabetes and identifying patients at increased risk of developing diabetes in the future. HbA1c reflects the level of blood glucose to which the erythrocyte has been exposed during its lifespan, and there are a number of clinical situations affecting the erythrocyte life span in which HbA1c values may be spuriously high or low and therefore not reflective of the true level of glucose control. In the present case series, we describe the particulars of three patients with diabetes who had spuriously low HbA1c levels as a result of dapsone usage. Furthermore, we discuss the limitations of HbA1c testing and the mechanisms by which it may be affected by dapsone in particular. Learning points: Various conditions and medications can result in falsely low HbA1c. Dapsone can lead to falsely low HbA1c by inducing haemolysis and by forming methaemoglobin. Capillary glucose measurement, urine glucose measurements and fructosamine levels should be used as alternatives to HbA1c for monitoring glycaemic control if it was falsely low or high.